The Effects of the COVID-19 Pandemic on Educational Attainment - Douglas N. Harris; Feng Chen; Rylie C. Martin; Ann F. Bernhardt; Christopher R. Marsicano; Paul T. von Hippel (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2024)
We study the effects of the COVID pandemic on educational attainment. By 2022, entry into two-year colleges was 21 percent lower than before the pandemic, with larger declines in Black- and Hispanic-majority colleges. Four-year college entry declined by only 6 percent and then rebounded 4 percent. High school graduation reached an all-time high in 2022. To explain these patterns, we undertook an interrupted time series design. Lower numbers of COVID cases and higher levels of in-person instruction led to increased college entry and possibly increased graduation. Relaxation of graduation standards explain between-state variation in high school graduation and helps explain the continued high graduation rates. Changing labor-market opportunities do not explain cross-state variation in attainment. We suggest additional explanations for these trends. Barring other substantial changes, we predict that future college attainment will be lower for cohorts of school or college age during the pandemic, especially for some marginalized groups.